Oral health and nutritional status of children in developing countries: A scoping review - Putriyani, Yuni; Shaluhiyah, Zahroh; Winarni, Sri (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Oral diseases, especially caries and malnutrition, are two major problems the world faces in developing countries. World Health Organization (WHO) report 2019 states that caries is the first non-communicable disease (NCD) suffered by children worldwide. In addition, malnutrition rates are still very high and most of them are in low-income countries. Many studies have suggested a relationship between oral health and children's nutritional status. However, the relationship between the two has not been consistent. Therefore, we conducted a scoping review to learn more about the relationship in developing countries. We obtained a total of 1,707 articles published in the last 10 years from two databases, Scopus and Science Direct. Ten relevant articles, written in English and published from 2015 to 2024, were reviewed and satisfied the inclusion criteria: a study about the relationship between oral health problems and nutritional status of 6 years old children and below who live in developing countries,. The 10reviewed articles were taken from eight developing countries in which nine articles used a cross-sectional design and only one article used a longitudinal cohort design. The results of the review shows that caries status studies related to nutritional status are five studies. Meanwhile, the remaining 5 articles shows no substantial relationship. In this scope, we used BMI (Body Mass Index) as an indicator for nutritional status. Further research is still needed, particularly in a longitudinal cohort design to get a clearer understanding of the causal relationship between both.